Analisis Efektivitas Pembelajaran Pengantar Ekonomi Mikro melalui Case Base Method dengan Pendekatan SEEQ - Tri Kurniawati; Yuhendri Leo Vrista; Mentari Ritonga; Wening Patmi Rahayu; Nurul Hidayati; Putri Rahmayanti (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2022)
This research aims to analyze the effective learning of introducing microeconomic courses through the implementation case base method with students' evaluation of the Educational Quality (SEEQ) approach. The research type is classroom action research with Sprial of Kemmis & Mc Taggart model. The result shows that case base method implementation can increase learning effectiveness. Recommended to the lecturer of the introduction of microeconomics course to use learning case base method as increasing learning effectiveness to getting learning outcomes.